(untitled) (Bangladesh Journal of Pharmacology, 2024)
This study aims to investigate the effect of berberine on necroptosis in cervical H8 cells. CCK-8 assay was used to assess cell proliferation activity. The expression levels of necroptosis key markers Receptor-interacting protein kinase 1 (RIPK1), MLKL, p-MLKL, and apoptosis-related caspase-8, caspase-3 were analyzed through qRT-PCR, western blot, and immunofluorescence. Mechanistic studies were conducted using the RIPK1 kinase inhibitor necrostatin-1 (Nec-1). The results showed that berberine could inhibit H8 cell proliferation in a time- and dose-dependent manner (p<0.05). It increased the expression of RIPK1 and MLKL (p<0.05), while inhibiting the expression of caspase-8 and caspase-3 (p<0.05). Nec-1 inhibitor decreased the expression of RIPK1 and MLKL after the intervention of berberine (p<0.05). Therefore, berberine induces cervical H8 cell death through the activation of RIPK1-mediated necroptosis.